Bundling subsurface drip irrigation with no-till provides a window to integrate mung bean with intensive cereal systems for improving resource use efficiency - Kakraliya, Manish; Jat, Hanuman S.; Kumar, Suresh; Kakraliya, Suresh Kumar; Gora, Manoj Kumar; Poonia, Tanuja; Kumar, Satyendra; Choudhary, Madhu; Gathala, Mahesh Kumar; Sharma, Parbodh Chander; Jat, M. L. (Frontiers in Sustainable Food Systems, 2024)
The future of South Asia's major production system (rice-wheat; RW rotation) is at stake due to continuously aggravating pressure on groundwater aquifers and other natural resources which will further intensify with climate change. Traditional practices; conventional tillage (CT) residue burning and indiscriminate use of groundwater with flood irrigation (FI) are the major drivers of non-sustainability of RW system in north-west (NW) India. For designing sustainable practices in intensive cereal systems, we conducted a study on bundled practices (zero tillage, residue mulch, precise irrigation and mungbean integration) based on multi-indicator (system productivity, profitability, and efficiency of water, nitrogen & energy) analysis in RW system. The study showed that bundling conservation agriculture (CA) practices with subsurface drip irrigation (SDI) saved 70 and 45% (3-yr mean) of irrigation water in rice and wheat, respectively compared to CT practice (pooled of Sc1 and Sc2; 1035 and 318 mm ha-1). On a 3-year system basis, CA with SDI scenarios (mean of Sc5-Sc8) saved 35.4% irrigation water under RW systems then their respective CA with FI scenarios (mean of Sc3 and Sc4) irrespective of residue management. CA with FI system increased the water productivity (WPi) and its use efficiency (WUE) by 52 and 12.3% (3-yr mean), whereas SDI improved by 221.2 and 39.2% then Sc1 (0.69 kg grain m-3 and 21.39 kg grain ha -1 cm -1 ), respectively. Based on 3-years mean, CA with SDI recorded -2.5% rice yield, whereas, wheat yield was +25% then Sc1 (5.44 and 3.79 Mg ha-1). Whereas, rice and wheat yield under CA with FI were increased by +7 and +11%, then respective CT practices. Mungbean integration in Sc7 and Sc8 contributed to 26% in crop productivity and profitability then Sc1 as SDI facilitated advancing the sowing time by one week. On a system basis, CA with SDI improved energy use efficiency (EUE) by 70% and partial factor productivity of N by 18.4% compared to CT practices. In RW system, CA with SDI proved to be a profitable solution to address the issues of groundwater, burning, sustainable intensification and input use with the potential in large areas of NW India.